PENINGKATAN KEMAMPUAN MEMBACA KITAB KUNING BERBASIS METODE AL-MIFTAH BAGI SANTRI DI PONDOK PESANTREN AL-AWWABIEN KELURAHAN TANJUNG PASIR KOTA JAMBI - Zahid, Muhammad Hilman; Kartubi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read kitab kuning is a fundamental competence for Islamic boarding school students in understanding classical Islamic scholarship. However, many students experience difficulties due to limited mastery of Arabic grammar, particularly nahwu and sharaf. This study aims to examine the improvement of students’ ability to read kitab kuning through the application of the Al-Miftah method at Al-Awwabien Islamic Boarding School, Tanjung Pasir, Jambi City. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, with data validity ensured through triangulation. The findings indicate that the systematic and gradual implementation of the Al-Miftah method emphasizing the reinforcement of nahwu and sharaf rules and supported by the use of nadzam significantly enhances students’ understanding of Arabic grammatical structures. Moreover, the method fosters students’ independence and confidence in reading kitab kuning. These results suggest that the Al-Miftah method is an effective instructional approach for strengthening traditional Islamic learning in contemporary pesantren contexts.